Meta Analysis of Clinical Efficacy of Traditional Chinese Medicine Compounds of Huoxue Yangyin in the Treatment of Vocal Cord Polyp after Surgery - GE Xiaoni; ZHU Ling; SONG Ruohui; TU Yanhong; ZHENG Rixin (康复学报)
ObjectiveTo evaluate the clinical efficacy and safety of the traditional Chinese medicine compounds "Huoxue Yangyin" for promoting blood circulation and nourishing Yin in the treatment of postoperative discomfort of vocal cord polyp by Metaanalysis.MethodsData were searched from the databases of China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP) ,Wanfang Database (Wanfang Data), China Biomedical Literature Database, PubMed, Embase, Web of science,Springer and Cochrane Library,etc. The patients with vocal cord polyp after surgery in the clinical randomized controlled trials (RCTs) were included who were treated with promoting blood circluation and nourishing Yin drugs. The retrieval time for each database was from January 2000 to May 2021. The outcome indicators including clinical efficacy, clinical symptom subsidence time, clinical symptom score, voice acoustic analysis, grade rough breathy asthenic strained (GRBAS), adverse reactions. RevMan 5.4.1 software was used for data analysis, continuous variables were expressed by weighted mean difference (WMD) and 95% confidence interval (CI); binary variables were expressed by odds ratio (OR) and 95% CI. If the included studies were homogeneous (I2<50%), a fixed effects model would be used; if the included studies were heterogeneous (I2≥50%), a random-effects model would be used.ResultsA total of 1 628 patients were included in 15 RCTs, including 813 in the experimental group and 815 in the control group. Meta analysis results showed that the total effective rate of the experimental group was significantly higher than that of the control group [OR=4.79, 95% CI (3.15, 7.26), P<0.000 01]; the symptom subsidence time in the experimental group was significantly lower than that of the control group [MD=-2.27, 95% CI (-2.48, -2.05), P<0.000 01]; the scores of clinical symptoms of the experimental group such as hoarseness,foreign body sensation, pain, cough, and dryness were lower than those of the control group (P<0.05); the voice acoustic parameters of the experimental group such as Jitter and Shimmer were significantly lower than those of the control group (P<0.05); the GRBAS score of the experimental group after treatment was significantly lower than that of the control group, and the difference was statistically significant [MD=-0.64, 95% CI (-0.79, -0.49), P<0.000 01]. There were no serious adverse reactions in both groups.ConclusionThe traditional Chinese medicine compounds of promoting blood circulation and nourishing Yin has a good effect in the treatment of vocal cord polyp after surgery, which can effectively improve postoperative hoarseness, foreign body sensation, pain, cough, dryness and other symptoms, and shorten the recovery time of vocal cord function.